2022
DOI: 10.1186/s12978-022-01519-2
|View full text |Cite
|
Sign up to set email alerts
|

“I am not shy anymore”: A qualitative study of the role of an interactive mHealth intervention on sexual health knowledge, attitudes, and behaviors of South African adolescents with perinatal HIV

Abstract: Background South Africa has one of the highest burdens of adolescents with perinatally-acquired HIV (APHIV) in the world. APHIV in South Africa have limited access to sexual and reproductive health (SRH) education and services specific to their HIV status. When lacking comprehensive SRH education, APHIV are prone to sexual risk behaviors that can lead to unintended pregnancy, sexually transmitted infections, and HIV transmission. The use of mHealth interventions has been shown to deliver inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…The finding is comparable to the result from an evaluation study in the United States of America which reported a significant increase in the number of adolescents who approached their parents for discussions on different aspects of SRH, following a community-based SRH intervention [ 33 ]. The finding that adolescents are now more confident to engage their peers on SRH issues openly without fear of being stigmatized is similar to results from Northern Nigeria and South Africa [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 74%
“…The finding is comparable to the result from an evaluation study in the United States of America which reported a significant increase in the number of adolescents who approached their parents for discussions on different aspects of SRH, following a community-based SRH intervention [ 33 ]. The finding that adolescents are now more confident to engage their peers on SRH issues openly without fear of being stigmatized is similar to results from Northern Nigeria and South Africa [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 74%
“…From the above submissions, some learners in rural areas have committed suicide due to poverty. Poverty can have a profound impact on individuals and communities, including rural learners, and can contribute to increased rates of suicide (Bergam et al, 2022). In Zimbabwe rural areas such as Mahoto rural area where this study.…”
Section: Poverty Leads Rural Learners To Commit Suicidementioning
confidence: 99%
“…Although no significant differences in treatment retention were observed between the two sample groups, results showed that the intervention group performed significantly better in HIV knowledge than the control group at the endline. In an urban township in KwaZulu-Natal, South Africa, the InTSHA intervention, a WhatsApp-based programme developed to influence SRH knowledge among adolescents with perinatally acquired HIV, has also shown favourable results [21]. Qualitative interviews with participants aged 15 to 19 who received the Interactive Transition Support for Adolescents Living with HIV (InTSHA) intervention revealed positive feedback on the programme.…”
Section: Srh Knowledgementioning
confidence: 99%